COVID-19 and other respiratory tract infections at mass gathering religious and sporting events - Al-Tawfiq, J. A.; El-Kafrawy, S. A.; McCloskey, B.; Azhar, E. I. (Current Opinion in Pulmonary Medicine, 2022)
Purpose of review: Mass gathering (MG) religious events provide ideal conditions for transmission and globalization of respiratory tract infections (RTIs). We review recent literature on COVID-19 and other RTIs at recurring international annual MG religious and sporting events. Recent findings: Due to the COVID-19 pandemic organizers of MG religious and sporting events introduced risk-based infection control measures that limited transmission of RTIs. The 2020 and 2021 Hajj were conducted with limited numbers of pilgrims compared to the annual millions of pilgrims. The Tokyo 2020 Olympic and Paralympic Games were cancelled and held in 2021. The success of the COVID-19 countermeasures at the 2021 Hajj and 2021 Tokyo Olympics was based on implementing good public health and social measures alongside a comprehensive testing strategy. Summary: MG events are associated with transmission of a range of bacterial and viral RTIs. Introducing risk based a multitude of public health interventions can reduce transmission of SARS-CoV-2 and other RTIs.